Introduction: Symposium Honoring the Advocacy, Scholarship and Jurisprudence of Justice Ruth Bader Ginsburg - Franke, Katherine (Columbia Journal of Gender and Law, 2013)
I want to welcome back Justice Ginsburg to Columbia Law School. She has been a frequent visitor since her time here as a student in the late 1950s and again as a member of our faculty in the 1970s. I know she knows, but it is worth reiterating that she always has a home here at Columbia. Forty years and two weeks ago, on January 24, 1972, the Columbia Law School student newspaper reported an exciting development in the history of the law school- Dean Michael Sovern had announced the hiring of the first woman with full tenure to our law faculty. Under the headline “Law Faculty Selects First Woman Member,” the students wrote that “Ruth Ginsberg”-spelling her name wrong-“currently a professor at Harvard will be the first woman to hold a tenured professorship here. It is expected that she will teach courses in procedure, which is her specialty, as well as one course and one clinical seminar on Sex Discrimination.” The article here, and later on, framed Ruth Ginsburg’s expertise as procedure, not sex discrimination-and in fact she had been working with Hans Smit, whose passing we memorialized yesterday, on the Columbia Project on International Procedure. Mike Sovern told me yesterday that when he made her the offer to join the faculty, she insisted that she would come only if she could teach Civil Procedure-something the law school did not need as we already had a deep bench in that area. But she was adamant and he relented.